(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article discusses the efficiency of modern technologies and electronic devices in learning. This article emphasizes then need for organizing courses that accelerate practicing English teachers’ knowledge and provide with essential resources. The article concludes that creating such courses can greatly enhance the teaching experience for teachers and improve their language skills.